Bad kids the naughtiest children in history] - Robinson, Tony 1946- (Macmillan Children's Books, 2011)
So you're standing outside the Head Office, waiting to be told off for breaking a classroom window. You've got sweaty palms and a serious sinking feeling in your stomach. All through history, children have been getting of into some serious scrapes. And they did not often get off lightly
Originally published : 2009
Keywords: Problem children / History / Juvenile literature; Problem children / Social conditions / Juvenile literature; Juvenile delinquency / History / Juvenile literature; Discipline of children / History; Discipline of children; Juvenile delinquency; Problem children; Problem children / Social conditions; Geschichte